Pengujian Model Peranan Kecakapan Hidup terhadap Kesehatan Mental - Hadjam, M. Noor Rochman; Widhiarso, Wahyu (Jurnal Psikologi, 2011)
The aim of this study was to test conceptual model that showed the role of life skills to mental health. Participants of this study was teachers (N=260) from various provinces in Indonesia who are following event by Diknas in Jakarta. Life skills was measured by Life Skills Scale that consist six life skill dimensions, while mental health was measured by the Life Satisfaction Scale and Quality of Life Scale. Those measurement model each variables was tested by measurement model of Structural Equation Model/SEM that produces the fit model (χ2=23.20; p>0:05 and χ2=11.54; p>0.05). Analysis using SEM showed that model has goodness fit indices (χ2=52.13 p>0.05). The role of life skills that includes six dimensions:emotional skills, social skills, self-esteem, communication, critical thinking and problem solving are able to predict individual mental health. These results provide strong support tothe activities of mental health improvement of individuals through life skills programs.